Calcium Binding to the Innate Immune Protein Human Calprotectin Revealed by Integrated Mass Spectrometry - Adhikari, Jagat (J Am Chem Soc, 2020)
Although knowledge of the coordination chemistry and metal-withholding function of the innate immune protein human calprotectin (hCP) has broadened in recent years, understanding of its Ca(2+)-binding properties in solution remains incomplete. In particular, the molecular basis by which Ca(2+) binding affects structure and enhances the functional properties of this remarkable transition-metal-sequestering protein has remained enigmatic. To achieve a molecular picture of how Ca(2+) binding triggers hCP oligomerization, increases protease stability, and enhances antimicrobial activity, we implemented a new integrated mass spectrometry (MS)-based approach that can be readily generalized to study other protein-metal and protein-ligand interactions. Three MS-based methods, HDX-MS, PLIMSTEX and native MS, provided a comprehensive analysis of Ca(2+) binding and oligomerization to hCP without modifying the protein in any way. Integration of these methods allowed us to (i) observe the four regions of hCP that serve as Ca(2+) binding sites, (ii) determine the binding stoichiometry to be four Ca(2+) per CP heterodimer and eight Ca(2+) per CP heterotetramer, (iii) establish the protein-to-Ca(2+) molar ratio that causes the dimer-to-tetramer transition, and (iv) calculate the binding affinities associated with the four Ca(2+)-binding sites per heterodimer. These quantitative results support a model in which hCP exists in its heterodimeric form and is at most half-bound to Ca(2+) in the cytoplasm of resting cells. With release into the extracellular space, hCP encounters elevated Ca(2+) concentrations and binds more Ca(2+) ions, forming a heterotetramer that is poised to compete with microbial pathogens for essential metal nutrients.